RTiK-Linux: 리눅스용 실시간 이식 커널의 설계 - 김주만; 송창인; 이철훈; Kim, Joo-Man; Song, Chang-In; Lee, Cheol-Hoon (한국콘텐츠학회 논문지, 11(9), 2011)
According to the necessity of measuring equipments for advanced military systems, real-time characteristics such as time determinism and execution accuracy pursuing low-latencies have become very important. With this reason, the market demand for real-time features in the general purpose operating system such as Linux has been enlarging. To meet these requirements, RTLinux and RTAI has been developed as dual-kernels based on Linux. However, developers should use assembler languages to facilitate real-time in RT-Linux, it is very difficult to deal with it. RTAI has disadvantage that it only provides soft real-time. To solve these problems, RTiK-Linux was developed. In this paper, we propose a new dual-kernel with hard real-time capabilities in Linux, called RTiK-Linux(Real-Time implemented Kernel for Linux). We first introduce related researches and then describe the design methodologies to guarantee the resolution which almost accords with the timer settings. Finally, we present the results of experimental measurements and analyze them in order to validate and evaluate the proposed RTiK-Linux. 첨단 군사 체계를 위한 측정 장치의 필요성에 따라 낮은 지연을 추구하는 실시간 특성인 시간 결정성과 수행의 정확성은 매우 중요해 졌으며, 이러한 이유로 리눅스와 같은 범용 운영체제에 실시간 기능을 추가하는 시장 요구가 증대하게 되었다. 따라서 RTLinux와 RTAI가 리눅스기반의 이중 커널로 개발되었다. RT-Linux의 경우 경성 실시간성을 제공하지만 어셈블러를 사용해야함으로 개발자가 다루기 어려운 단점이 존재한다. 또한 RTAI의 경우 연성 실시간성만을 제공하는 단점이 있다. 이러한 단점을 해결하기 위해 RTiK-Linux를 개발하였다. 본 논문에서는 리눅스에 경성 실시간 특징을 가지며 새로운 이중 커널 구조인 실시간 이식 커널인 RTiK-Linux를 제안한다. 먼저 관련 연구에 대한 소개를 하고, 타이머 설정 값과 거의 일치하는 분해능을 보장하는 설계 방법론을 기술한다. 그리고 경험적 측정으로 얻어진 결과를 보이고, 제안하는 RTiK-Linux를 검증 및 평가하기 위하여 그 결과를 분석한다.